2013
DOI: 10.1213/ane.0b013e318294820f
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Bolus Dose of Intravenous Lidocaine on the Minimum Alveolar Concentration of Sevoflurane

Abstract: IV 1.5 mg·kg(-1) lidocaine decreased the MAC by at least 0.03% sevoflurane (mean difference 0.23% sevoflurane [95% adjusted CI, 0.03-0.43]). We did not observe a significant reduction in the MAC of sevoflurane with the IV administration of 0.75 mg·kg(-1) lidocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
2
18
0
1
Order By: Relevance
“…The use of IV lignocaine has been shown to be associated with a reduced requirement of intravenous anaesthetic agents, specifically propofol [1215]. Intravenous lignocaine has also been shown to reduce the requirements of volatile anaesthetics in patients undergoing non-abdominal surgeries [1618], findings similar to the present study. Interestingly, even the delivery of lignocaine via both the epidural and IV routes has been shown to reduce requirement of volatile anaesthetics [19, 20].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The use of IV lignocaine has been shown to be associated with a reduced requirement of intravenous anaesthetic agents, specifically propofol [1215]. Intravenous lignocaine has also been shown to reduce the requirements of volatile anaesthetics in patients undergoing non-abdominal surgeries [1618], findings similar to the present study. Interestingly, even the delivery of lignocaine via both the epidural and IV routes has been shown to reduce requirement of volatile anaesthetics [19, 20].…”
Section: Discussionsupporting
confidence: 84%
“…In laparoscopic abdominal surgery, IV lignocaine has reduced the average concentration of volatile anaesthetic agents by more than 35% [21, 22]. However, to our knowledge, in the context of major open abdominal surgery only two studies have evaluated the effects of IV lignocaine on the concentration of volatile anaesthetic required to maintain anaesthesia [16, 20]. Hamp et al found that the mean alveolar concentration of sevoflurane was 12% lower in those receiving a bolus dose of 1.5 mg/kg of intravenous lignocaine [13, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sevoflurane requirement was significantly reduced during abdominal surgery as monitored by BIS at all intraoperative time points [11]. The same result was found in different types of surgeries using sevoflurane [7,11,32,34] and desflurane [6,22,27]. Similarly, systemic lidocaine allowed Altermatt et al to reduce propofol requirement during the maintenance of total intravenous anesthesia for laparoscopic cholecystectomy as measured by BIS.…”
Section: Discussionmentioning
confidence: 70%
“…Intravenous lidocaine increases the depth of anesthesia of propofol and of sevoflurane [66,67]. Perioperative administered lidocaine intravenous as a bolus or as a continuous infusion and for local or regional anesthesia reduces pain before, during, and after operations and procedures [43,[68][69][70].…”
Section: Intravenous and Topical Lidocainementioning
confidence: 99%